BERDAQ SHIǴARMALARINDA FRAZEOLOGIYALIQ SÓZ DIZBEKLERI TIYKARINDA PAYDA BOLǴAN SINONIMLER - Kurbanbaeva, P. (SCIENCE and SOCIETY, 2022)
The article talks about the emotional-expressive, stylistic use of phraseological synonyms in the works of the poet Berdaq. In particular, it was analyzed that phraseological synonyms are used the most among synonyms in the language of Berdaq's works.